Bayt Mal and The Real Sector in The View Of Islamic - Putra Halomoan Hsb; Erwin Pane (Saqifah: Jurnal Hukum Ekonomi Syariah, 2024)
Utilizing a mixed-methods approach, This study explores the role of Bayt Mal (Islamic treasury) in fostering the real sector within an Islamic economic framework. The research integrates qualitative and quantitative methodologies to provide a comprehensive analysis. Qualitative data were gathered through in-depth interviews with Islamic finance experts, scholars, and practitioners, providing insights into the operational mechanisms and challenges faced by Bayt Mal in modern economic contexts. Quantitative data were derived from financial reports and economic indicators to assess the impact of Bayt Mal on various sectors, including agriculture, trade, and manufacturing. The findings reveal that Bayt Mal is crucial in resource mobilization and distribution, promoting economic justice and social welfare. However, regulatory constraints, lack of awareness, and inefficient management practices hinder its potential. The study concludes with recommendations for enhancing the effectiveness of Bayt Mal, emphasizing the need for robust governance structures, increased public awareness, and integration with contemporary financial systems to optimize its contribution to the real sector and achieve sustainable economic development in line with Islamic principles.